2011
DOI: 10.3892/ijo.2011.1063
|View full text |Cite
|
Sign up to set email alerts
|

Opioids increase bladder cancer cell migration via bradykinin B2 receptors

Abstract: Abstract. Data relating opioid treatment and modification of cancer cell migration (a prerequisite of metastasis) both in vitro and in vivo are diverging. In the present report we show that opioids increase the migratory activity of bladder cancer cells (T24 and EJ) and we provide a new mechanistic insight, explaining (at least partially) their action: we report that the enhanced opioid-related cell migration is controlled (in the absence of opioid receptors) through their interaction with bradykinin B2 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Several recent studies indicated that BK can promote proliferation, invasion, and migration in different cell types via BK receptors, suggesting that BK receptors play critical roles in tumor metastasis [1820]. Interestingly, the B2 receptor, rather than the B1 receptor, is commonly involved in most biological actions that are BK-mediated [20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies indicated that BK can promote proliferation, invasion, and migration in different cell types via BK receptors, suggesting that BK receptors play critical roles in tumor metastasis [1820]. Interestingly, the B2 receptor, rather than the B1 receptor, is commonly involved in most biological actions that are BK-mediated [20,21]. …”
Section: Introductionmentioning
confidence: 99%